2005
DOI: 10.1161/01.res.0000157171.04054.30
|View full text |Cite
|
Sign up to set email alerts
|

Association Between a Functional Variant of the KLOTHO Gene and High-Density Lipoprotein Cholesterol, Blood Pressure, Stroke, and Longevity

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
211
4
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 28 publications
13
211
4
10
Order By: Relevance
“…This observation may be explained by the relatively small number of BRCA1 patients who harbored the VV genotype. Interestingly, a study of Ashkenazi Jews also showed differential effects of heterozygosity compared with homozygosity for the V allele (Arking et al, 2005). Thus, heterozygous individuals were at significantly lower risk for stroke, whereas homozygous individuals had significantly higher risk compared with wild-type individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This observation may be explained by the relatively small number of BRCA1 patients who harbored the VV genotype. Interestingly, a study of Ashkenazi Jews also showed differential effects of heterozygosity compared with homozygosity for the V allele (Arking et al, 2005). Thus, heterozygous individuals were at significantly lower risk for stroke, whereas homozygous individuals had significantly higher risk compared with wild-type individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study on Ashkenazi-Jewish populations replicated the heterozygous advantage but not the homozygous disadvantage (Arking et al 2005) ( Table 2).…”
Section: Introductionmentioning
confidence: 87%
“…Changes in KL gene expression would, over time, impact normal function of all downstream pathways. Evidence of such an effect is observed in the KL polymorphism KL VS (Arking et al 2002) where slight changes in KL function increases risk of disease (Arking et al 2002(Arking et al , 2003(Arking et al , 2005Invidia et al 2010;Wolf et al 2010). Of course, the overall contribution of a small change in one gene would not induce a dramatic phenotype in humans as it does in the KL knockout mouse; however, small changes in KL and numerous other genes would add up over time.…”
Section: Many Small Changes Can Affect Gene Expressionmentioning
confidence: 99%